Bare Nouns in the Typology of DPs - Paul, Ileana (Linguistica Atlantica, 2004)
This paper investigates two types of bare nouns in Malagasy: bare nouns in possessor raising contexts and bare noun objects. It is argued that these two types are structurally distinct. In possessor raising, the bare noun is in fact an NP, lacking a DP layer. Bare noun objects, on the other hand, are DPs with a null determiner. These structural differences can be seen to have both syntactic and semantic consequences.